Barriers and facilitators to the use of the mental health information system in Ghana: A qualitative study amongst users at the Accra Psychiatric Hospital - Kpobi, Lily Naa Ayorkor (Stellenbosch : Stellenbosch University, 2015)
Thesis (MA)--Stellenbosch University, 2015